2020
DOI: 10.1101/2020.06.29.178509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike glycoprotein vaccine candidate NVX-CoV2373 elicits immunogenicity in baboons and protection in mice

Abstract: AbstractThe COVID-19 pandemic continues to spread throughout the world with an urgent need for a safe and protective vaccine to effectuate herd immunity to control the spread of SARS-CoV-2. Here, we report the development of a SARS-CoV-2 subunit vaccine (NVX-CoV2373) produced from the full-length spike (S) protein, stabilized in the prefusion conformation. Purified NVX-CoV2373 S form 27.2nm nanoparticles that are thermostable and bind with high affinity to the human angiotensin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 26 publications
0
130
0
Order By: Relevance
“…are made in baculovirus, the insect cell produce protein with man-9 glycosylation that may be sufficient for immune response induction, but may not recapitulate the antigenicity of virus grown in mammalian cells [5,[18][19]. Animal challenge studies will be conducted at a future date to examine the safety and efficacy of our candidate vaccine.…”
Section: Although the Leading Subunit Protein Covid-19 Vaccines By Dementioning
confidence: 99%
“…are made in baculovirus, the insect cell produce protein with man-9 glycosylation that may be sufficient for immune response induction, but may not recapitulate the antigenicity of virus grown in mammalian cells [5,[18][19]. Animal challenge studies will be conducted at a future date to examine the safety and efficacy of our candidate vaccine.…”
Section: Although the Leading Subunit Protein Covid-19 Vaccines By Dementioning
confidence: 99%
“…Multiple studies employing a variety of vaccine formulations and modalities have now demonstrated that SARS-CoV-2 viral neutralization titers in small animals including mice and guinea pigs are predictive of immunogenicity in macaques and humans ( Figure 5E) [17][18][19][20]22,23,[33][34][35][36][37][40][41][42][43]45 . Despite promising immunogenicity in several cases, all of the above liquid formulations were either refrigerated or frozen prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Pichia expressed RBD was as immunogenic as the mRBD in terms of self-titers (Supplementary Figure 3A, 3B) but sera reacted poorly with mRBD and Spike-2P. Several studies have now shown that ACE2 competition titers and neutralizing antibody titers are highly correlated 22,31 . Hence serum competition assays were carried out ( Figure 5C).…”
Section: Addavax™ Adjuvanted Rbd Elicits Neutralizing Antibodies In Gmentioning
confidence: 92%
See 2 more Smart Citations